Evaluating hedge fund and CTA performance : data envelopment analysis approach - Gregoriou, Greg N., 1956- (J. Wiley, 2005)
Introducing Data Envelopment Analysis (DEA) -- a quantitative approach to assess the performance of hedge funds, funds of hedge funds, and commodity trading advisors. Steep yourself in this approach with this important new book by Greg Gregoriou and Joe Zhu.